Influencing Factors of Tourism Enterprise Collaboration on Huzhou Tourism Participation Development under the Background of Cultural and Tourism Integration - Weiqi Li (International Forum of Researchers and Lecturers, 2025)
The topic of factors influencing tourism enterprise cooperation on the development of tourism participation in Huzhou under the background of cultural and tourism integration can be explored from multiple dimensions, highlighting the interaction between tourism enterprises and the broader cultural context of Huzhou. One important aspect is the importance of cultural heritage in promoting tourism participation. Known for its rich cultural resources and historical significance, incorporating cultural elements into the tourism industry can enhance the tourist experience and encourage more people to participate in tourism activities. This study, conducted through an online questionnaire distributed to 380 participants in Huzhou, delves into the impact of cultural and tourism integration on tourism development and strategies to manage tourism participation. The findings underscore that factors influencing cultural and tourism integration, government support and policy, and cooperative mechanisms positively correlate with tourism participation and enterprise collaboration in Huzhou.